Immune-Mediated Systemic Vasculitis as the Proposed Cause of Sudden-Onset Sensorineural Hearing Loss following Lassa Virus Exposure in Cynomolgus Macaques - Kathleen A. Cashman (American Society for Microbiology, 2018)
ABSTRACT Lassa virus (LASV) causes a severe, often fatal hemorrhagic disease in regions in Africa where the disease is endemic, and approximately 30% of patients develop sudden-onset sensorineural hearing loss after recovering from acute disease. The causal mechanism of hearing loss in LASV-infected patients remains elusive. Here, we report findings after closely examining the chronic disease experienced by surviving macaques assigned to LASV exposure control groups in two different studies. All nonhuman primates (NHPs) developed typical signs and symptoms of Lassa fever, and seven succumbed during the acute phase of disease. Three NHPs survived beyond the acute phase and became chronically ill but survived to the study endpoint, 45 days postexposure. All three of these survivors displayed continuous disease symptoms, and apparent hearing loss was observed using daily subjective measurements, including response to auditory stimulation and tuning fork tests. Objective measurements of profound unilateral or bilateral sensorineural hearing loss were confirmed for two of the survivors by brainstem auditory evoked response (BAER) analysis. Histologic examination of inner ear structures and other tissues revealed the presence of severe vascular lesions consistent with systemic vasculitides. These systemic immune-mediated vascular disorders have been associated with sudden hearing loss. Other vascular-specific damage was also observed to be present in many of the sampled tissues, and we were able to identify persistent virus in the perivascular tissues in the brain tissue of survivors. Serological analyses of two of the three survivors revealed the presence of autoimmune disease markers. Our findings point toward an immune-mediated etiology for Lassa fever-associated sudden-onset hearing loss and lay the foundation for developing potential therapies to prevent and/or cure Lassa fever-associated sudden-onset hearing loss. IMPORTANCE Lassa virus is one of the most common causes of viral hemorrhagic fever. A frequent, but as yet unexplained, consequence of infection with Lassa virus is acute, sudden-onset sensorineural hearing loss in one or both ears. Deafness is observed in approximately 30% of surviving Lassa fever patients, an attack rate that is approximately 300% higher than mumps virus infection, which was previously thought to be the most common cause of virus-induced deafness. Here, we provide evidence from Lassa virus-infected cynomolgus macaques implicating an immune-mediated vasculitis syndrome underlying the pathology of Lassa fever-associated deafness. These findings could change the way human Lassa fever patients are medically managed in order to prevent deafness by including diagnostic monitoring of human survivors for onset of vasculitides via available imaging methods and/or other diagnostic markers of immune-mediated vascular disease.